Synchrotron-Based Three-Dimensional Fourier-Transform Infrared Spectro-Microtomography of Murchison Meteorite Grain. Issue 6 (June 2017) - Yesiltas, Mehmet; Sedlmair, Julia; Peale, Robert E.; Hirschmugl, Carol J.
We demonstrate nondestructive, three-dimensional, microscopic, infrared (IR) spectral in-situ imaging of an extraterrestrial sample. Spatially resolved chemical composition and spatial correlations are investigated within a single 45 µm grain of the Murchison meteorite. Qualitative and quantitative investigation through this analytical technique can help elucidate the origin and evolution of meteoritic compounds as well as parent body processes without damaging or altering the investigated samples.